Meningkatkan Hasil Belajar Siswa Melalui Pembelajaran Kooperatif STAD Berdasarkan Pengelompokan Gaya Belajar pada Siswa Kelas XI SMA Negeri 8 Makassar - Fatmawati, . (bionature, 2009)
This research aim to know increase of achievement student class XIB SMAN 8 Makassar who taught through the cooperative learning The Technique of STAD by grouping of student based on their learning style This classroom action research consists of two cycles; the implementation includes the planning, action, observation and reflection. Cycle I and II were four meetings. This research was conducted in odd semester 2008/2009 with the subject of students as many 35 people. Data of students' learning style were collected from questionnaire results to identify learning style of each student. Student learning outcomes data obtained from tests of learning outcomes at the end of each cycle. Student activity data obtained from two observers using the observation sheet. The results showed that the average student activity has increased the percentage of the cycle I to cycle II. Overall student learning outcomes and according of learning method to increase from cycle I to cycle II. Concluded that the results of studying biology grade students SMA Negeri 8 Makassar XIB was increased after application of cooperative learning The Technique of Student Team Achievement Division by classifying students based on learning style.Â